2019
DOI: 10.1155/2019/4101695
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment on Selected Physicochemical Parameters and Antioxidant and Antimicrobial Activities of Honey Samples from Selected Districts of the Amhara and Tigray Regions, Ethiopia

Abstract: The composition and properties of natural honeys differ with plant species on which the bees forage and the climatic conditions of the production areas. In Ethiopia, Amhara and Tigray are neighboring regions consisting of different agricultural activities and blossoms from different types of vegetations which may influence the natural composition and hence the properties of honey. So, the aim of the current study was to assess the quality of honey from selected districts of the two regions. In the study, 18 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Several researchers indicated that the color of honey is a reliable index of antioxidant activity and this sensory parameter is dependent on chemicals such as polyphenols and mineral content [ 18 , 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers indicated that the color of honey is a reliable index of antioxidant activity and this sensory parameter is dependent on chemicals such as polyphenols and mineral content [ 18 , 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between honey color and antioxidant activity has also been proved [ 8 , 15 , 16 , 17 ]. To a lesser extent, environmental and climatic conditions, harvesting treatment and storage can also influence the antioxidant activity of honey [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Average ash mass fraction value was 0.13 ± 0.07%. High linear correlation between EC and ash mass fraction was found by many authors (Accorti, Piazza & Persano-Oddo, 1987;Thrasyvoulou, & Manikis, 1995;Kropf, Jamnik, Bertoncelj & Golob, 2008;El Sohaimy, Masry,& Shehata, 2015;Lewoyehu & Amare, 2019).…”
Section: Resultsmentioning
confidence: 77%
“…The close relationship between the color and antioxidant activity of honey has been confirmed by several research groups [13,[22][23][24]. Other factors that can have an impact on the antioxidant capacity of honey include environmental and climatic conditions, harvesting treatment, and storage [25]. Floral origin of honey was found to play a decisive role in its biological activities, regarding both antioxidant and antibacterial properties [4,15].…”
Section: Introductionmentioning
confidence: 74%